Substitution of hemoglobin levels in pregnant women with iron supplement: A prospective randomized clinical study - A. Daniilidis; G. Dryllis; G. Chorozoglou; M. Politou; R. Dampali; K. Dinas (IMR Press, 2020)
Introduction: Iron deficiency anemia (IDA) is the most common form of anemia. Women who are pregnant or lactating and young children are the most affected. Iron protein acetyl aspartilate is a ferroprotein complex that is more efficient versus iron protein succinylate in relatively short periods of time, for example 30 days. Objective: The aim of this clinical study was to investigate the efficacy of acetyl aspartate iron protein supplement in the treatment of anemia in pregnant women after the first trimester. This is the first real-time clinical study testing the usage of an iron protein supplement in a specific population, as there are not sufficient data for such studies in the literature. Study Design: 28 pregnant women with hemoglobin < 10.5 gr/dL and after completing the 12th week of pregnancy, initiated acetyl aspartate protein iron at a daily dose yielding 80g of elemental iron in two uptakes. Similarly, 35 women were studied who received different iron supplements at the same daily dose. After 30 days, hemoglobin values were measured. Inclusion criteria included: age > 18, gestational week > 12, Hb < 10.5 g/dL, Ht < 32%. Exclusion criteria included: age <18, pregnancy < 12 weeks, many pregnancies, history: allergy to iron preparations, ulcer, cirrhosis, hemodialysis, hemochromatosis, aplastic anemia, chronic disease anemia, pancreatitis, renal disease. Results: Treatment with acetyl aspartylated iron lead to higher levels of hemoglobin after four weeks of treatment. Following successive measurements of hemoglobin levels in the 28 women of the study group, Hb levels increased from an initial mean Hb value of 10.04 gr/dL to 10.69 gr/dL. In the control group of 35 pregnant women, an increase in the mean hemoglobin from Hb was observed from 9.99 gr/dL to 10.46 gr/dL. The difference was statistically significant with p < 0.0001. Conclusions: The use of acetyl aspartate iron protein is a very promising option, as there has been an increase in hemoglobin levels to 0.5 gr/dL.